Nature and Specificity of Gestural Disorder in Children with Developmental Coordination Disorder: A Multiple Case Study - Costini, Orianne; Roy, Arnaud; Remigereau, Chrystelle; Faure, Sylvane; Fossoud, Catherine; Le Gall, Didier (Frontiers in Psychology, 2017)
Aim: Praxis assessment in children with developmental coordination disorder (DCD) is usually based on tests of adult apraxia, by comparing across types of gestures and input modalities. However, the cognitive models of adult praxis processing are rarely used in a comprehensive and critical interpretation. These models generally involve two systems: a conceptual system and a production system. Heterogeneity of deficits is consistently reported in DCD, involving other cognitive skills such as executive or visual-perceptual and visuospatial functions. Surprisingly, few researches examined the impact of these functions in gestural production. Our study aimed at discussing the nature and specificity of the gestural deficit in DCD using a multiple case study approach. Method: Tasks were selected and adapted from protocols proposed in adult apraxia, in order to enable a comprehensive assessment of gestures. This included conceptual tasks (knowledge about tool functions and actions; recognition of gestures), representational (transitive, intransitive), and non-representational gestures (imitation of meaningless postures). We realised an additional assessment of constructional abilities and other cognitive domains (executive functions, visual-perceptual and visuospatial functions). Data from 27 patients diagnosed with DCD were collected. Neuropsychological profiles were classified using an inferential clinical analysis based on the modified t-test, by comparison with 100 typically developing children divided into five age groups (from 7 to 13 years old). Results: Among the 27 DCD patients, we first classified profiles that are characterised by impairment in tasks assessing perceptual visual or visuospatial skills (n = 8). Patients with a weakness in executive functions (n = 6) were then identified, followed by those with an impaired performance in conceptual knowledge tasks (n = 4). Among the 9 remaining patients, 6 could be classified as having a visual spatial/visual constructional dyspraxia. Gestural production deficits were variable between and within profiles. Discussion: This study confirmed the heterogeneity of gestural production deficit among children with a diagnosis of DCD, at both intra- and inter-individual levels. The contribution of other cognitive deficits in most of the profiles allows discussing the specificity of gestural difficulties. This argues in favour of the necessity to distinguish gestural problems with other deficits made apparent through gesture.